La visita del oidor Luxan de Vargas a la jurisdicción de Córdoba del Tucumán (1692-1693): práctica de la justicia y disputa de valores - Bixio, Beatriz (Revista Española de Antropología Americana, 2007)
A first approach to the visita of the Oidor of the Audience of Charcas, Antonio Martínez Luxan de Vargas, to the jurisdiction of Córdoba del Tucumán. The aim consists in determining the way justice operates in the viceroyalty, where the institution of encomienda had resulted in a system obtained from the use and custom, with notorious features which remained out of the law in force.